2020
DOI: 10.1007/s00520-020-05816-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for allogeneic haematopoietic stem cell transplantation: how much benefit is worthwhile from the patient’s perspective?

Abstract: Oncological studies have shown that patients consider small benefits sufficient to make adjuvant chemotherapy worthwhile. We sought to determine the minimal survival benefits that patients considered enough to legitimate allogeneic haematopoietic stem cell transplantation (HCT) and the factors associated with patient preferences. One hundred eighty-four patients having previously received allogeneic HCT at our centre were included and completed a questionnaire exploring patient expectations elicited by time tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our results reveal that less than 10% of HSCT survivors regret having a transplant. This is consistent with previous U.S. surveys which report rates of decisional regret between 1% and 15% ( Cusatis et al, 2020 ; Leuthold et al, 2021 ; Mosher et al, 2011 ). In many ways, of course, this is unsurprising given the life-saving nature of transplant and the limited treatments options that are generally open to the vast majority of patients at the time that they are recommended to undergo HSCT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results reveal that less than 10% of HSCT survivors regret having a transplant. This is consistent with previous U.S. surveys which report rates of decisional regret between 1% and 15% ( Cusatis et al, 2020 ; Leuthold et al, 2021 ; Mosher et al, 2011 ). In many ways, of course, this is unsurprising given the life-saving nature of transplant and the limited treatments options that are generally open to the vast majority of patients at the time that they are recommended to undergo HSCT.…”
Section: Discussionsupporting
confidence: 92%
“…Studies of the experience of survivors of cancer and transplantation have demonstrated that, in hindsight, some survivors come to regret the decision to proceed with treatment, particularly those who had a different treatment option open to them and whose quality of life (QoL), psychological and physical well-being, and relationships are diminished following treatment ( Leuthold et al, 2021 ). This feeling of discomfort or distress regarding a previous decision, in this case to proceed with a recommended course of treatment, is termed “decisional regret” ( Szproch & Maguire, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation